Protection of Migrant Workers under the ICMW: Incompatibility with Malaysian Laws and Position in ASEAN - Abdul Aziz, Saidatul Nadia; Mat Basir, Salawati (Hasanuddin Law Review, 2021)
The International Convention on The Protection of The Rights of All Migrant Workers and Members of Their Families (ICMW) is the only Human Rights Convention that distinguishes between normal and irregular migrants in great detail. An analysis of the situation in Malaysia, based on feedback from relevant stakeholders, shows that there are insurmountable obstacles to ratification in relation to the ambiguous policy status for migrant workers, which is based on ad hoc policies. Malaysian legislation appears to be straightforward in its approach to labour migration policies, as it defines and categorises migrants into two distinct ‘categories': registered migrant (regular migrant) and undocumented migrant (irregular migrant), regardless of ability level. This article demonstrates that, despite the barriers and incompatibilities with national laws, the Convention, which is primarily a human rights instrument aimed at protecting the fundamental rights of all migrants, could assist Malaysia in ensuring a holistic and sustainable migration management that takes into account the needs of a whole approach and support from all parties involved, including but not limited to the Malaysian government. Part I of the article will go through the history of the convention's adoption, followed by Part II on the state of Malaysia's migration laws and policies, Part III on the compatibility and incompatibility of Malaysian laws with the ICMW and the position in ASEAN, and Part IV on recommendations.